The Effect of High Temperature Roasted Coffea liberica on Physiological and Histological Structure of Mice’s Kidney - Ivolanesky Putri Widodo; Syamsurizal Syamsurizal; Diah Tri Utami (Indonesian Society for Cancer Chemoprevention, 2019)
Numerous varieties of coffee, such as robusta, arabica, gayo and etcetera, was made in order to fulfill the needs of its lovers. In Tungkal, Jambi, Liberica coffee was recently discovered and the chemical reactions during roasting process produces several components, which are caffeine, chlorogenic acid, monosaccharides and others, to create a unique flavor as the identity. Unique flavor of Liberica coffee is obtained from the high temperature roasting process and the components in coffee. This research aims to determine the effect of Liberica coffee (Coffea liberica), concentration (0, 8.000, 10.000 and 12.000 ppm/day) on the physiological and histological structure of the mice’s kidney (Mus musculus L.) for 28 days. The results was showed that kidney histological observation of fatty degeneration, tubular swelling, and pyknotic nucleus associated with percentages of renal tubular damage in the control group, P1, P2 and P3 were 0.71±0.96, 4.91±0.17, 5.82±0.21 and 9.01±0.13 indicating low damage (<50%) and liberica coffee does not affect physiological function, such as creatinine level.Keywords : Liberica coffee, kidney, histological